Physical Characterization of Lead Bismuth Borate and Lead Bismuth Phosphate Glasses - Muhammad @ Ahmad, Hamizan (2005)
Systematic series of lead bismuth borate (PbO - Bi203 - B2O3) and lead bismuth phosphate (PbO - Bi203 - P205) glasses were prepared using melt quenching technique, where PbO, Bi203, B2O3 and P205 contents changed in every series based on their weight percentage. Some physical properties were measured and their amorphous natures were confirmed earlier by the X-ray diffraction technique. The experimental results showed that the density @) of both glasses increased, for examples from 3920 kg/m3 to 6325 kg/m3 for A1 - A5 series in PbO - Bi203 - B203 glasses and from 4331 kg/m3 to 5698 kg/m3 for El - E5 series in PbO - Bi203 - P2O5 glasses. This was due to the replacement of Bi203 and PbO in the B2O3 and P2O5 in glassy networks. Additional increment of Bi203 and PbO in both types of glasses causing more discontinuity and hence, decreased in their rigidity and velocity. Meanwhile,there was also a similar pattern in elastic moduli in both glass systems, where the values increased at the earlier stage and then decreased subsequently. Both Young's and bulk modulus were related to the crosslinking density with large influence on the propagation of ultrasonic velocities. All glass samples were also found to have crosslink density of 1 and Poisson's ratio - 3 which was typical for the B203 and P205 glasses. In optical properties for both types of glasses, it was found that the shifting of wavelength was related to the amount of production of the non-bridging oxygen (NBO). The existence of less disorder in phosphate network contributed to higher values of glass optical band gap (E,,,). Conversely, the introduction of PbO and Bi203 cause great disorder happen in the borate network which results in lower Ew values. In this study, the values of Em decreased uniformly with increasing content of PbO and Bi203 for examples from 2.61 eV to 2.25 eV for B1 - B5 series in PbO - Bi203 - B2O3 glasses and from 3.71 eV to 3.06 eV for GI - G4 series in PbO - Biz03 - P205 glasses. The increases in NBOs will be accompanied by an increase in polarizability and refractive index (n). In most cases, the variation of n increases when the molar volume (Vm) decreases, however for PbO - Biz03 - B203 glasses, the increasing value of n for an example from 1.62 to 1.86 for C1 - C5 series is accompanied by an increased in.V, This discrepancy can be explained by assuming the increase in both of the Vm and p, was attributed to change occurred in the volume concentration of BO3 units. Results from thermal studies of the glass showed that values for glass transition temperature (T,) was closely related to the chemical bond in the system. For PbO - Bi203 - 8203 glasses, the ionic bond character became more dominant in the system with the addition of more pb2' and B? and hence decreases the T, of sample. However, in PbO - Bi203 - P2O5 glasses, the addition of pb2' and ~i~ not only failed to weaken the covalent character in P-O-P bonds, but strengthened it further which leads to an increment in T, values for an example from 30g°C to 352OC for F1 - F4 series.